2009
DOI: 10.1111/j.1752-1688.2009.00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change Impacts on Water Resources in the Upper Blue Nile River Basin, Ethiopia1

Abstract: Kim, Ungtae and Jagath J. Kaluarachchi, 2009. Climate Change Impacts on Water Resources in the Upper Blue Nile River Basin, Ethiopia. Journal of the American Water Resources Association (JAWRA) 45(6):1361‐1378. Abstract:  Climate change affects water resources availability of international river basins that are vulnerable to runoff variability of upstream countries especially with increasing water demands. The upper Blue Nile River Basin is a good example because its downstream countries, Sudan and Egypt, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
110
2
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(123 citation statements)
references
References 41 publications
7
110
2
1
Order By: Relevance
“…Climate change studies showed temperature increased and precipitation pattern changed throughout arid and semi-arid regions of Africa [30][31][32] and affected the hydrological processes that impacts reservoir operation. Most studies showed the impacts of climate change on African hydropower reservoirs [23,[33][34][35][36]. Kim and Kaluarachchi [33] and Beyene et al [34] projected that precipitation and temperature will be increased in the Nile River basin and have positive effect on hydropower production, but Yamba et al [35] and Hamududu and Killingtveit [36] investigated that in the next 60 years hydropower production show a gradual reduction with large variability in the Zambezi River basin.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change studies showed temperature increased and precipitation pattern changed throughout arid and semi-arid regions of Africa [30][31][32] and affected the hydrological processes that impacts reservoir operation. Most studies showed the impacts of climate change on African hydropower reservoirs [23,[33][34][35][36]. Kim and Kaluarachchi [33] and Beyene et al [34] projected that precipitation and temperature will be increased in the Nile River basin and have positive effect on hydropower production, but Yamba et al [35] and Hamududu and Killingtveit [36] investigated that in the next 60 years hydropower production show a gradual reduction with large variability in the Zambezi River basin.…”
Section: Introductionmentioning
confidence: 99%
“…Further, previous studies show that many parts of the Nile basin are sensitive to climatic variations (Conway and Hulme, 1996;Strzepek 1996, 1998a, b;Conway, 2005;Kim et al, 2008;Beyene et al, 2010) implying that climate change will have a considerable impact on the resource. Therefore, it is necessary to analyse the possible changes in the different water resources aspects under the changing climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Potential impact of climate change in the Nile basin has been studied using outputs from General Circulation Models (GCMs) by different researchers on different catchments of the basin during the previous years (Conway andHulme, 1993, 1996;Strzepek and Yates, 1996;Conway 2005;Kim et al, 2008;Beyene et al, 2010;Elshamy et al, 2009a, b;Elshamy and Wheater, 2009;Soliman, et al, 2008;Githui et al, 2009). The studies used different methods for translating specified changes in climatic inputs into changes in hydrological regimes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, [2] [3] studied climate change impact in Upper Blue Nile by direct use of GCM outputs ignoring aspects of the course scale resolution. It is described that hydrological impacts of climate change on the Lake Tana water balance are not well explored [2] [3]. Recently, by applying a perturbation downscaling approach of GCM outputs, [4] investigated the impact of climate change on high rainfall and flow extremes for the Nyando River and Lake Tana catchments in the Upper Blue Nile basin, Ethiopia.…”
Section: Introductionmentioning
confidence: 99%